Friction surfacing of aluminum alloy 5083-H112 over AA 2024-T3 - Silvério, Samuel Hernandes (2018)
Friction surfacing (FS) is an advanced solid-state process in surface modification with increasing applications in reclaiming worn parts, hardfacing and corrosion protection. It is considered a derivation of the friction stir welding process, keeping many benefits of the primary process such as: solid phase, forged microstructure and excellent metallurgical bond. As no melting takes place, the process allows dissimilar joining of materials while avoiding several fusion related problems. The present study addresses the deposition of AA5083-H112 coatings over AA2024-T3 substrates, focusing on the influence of the thermo-mechanical process in the mechanical properties and geometry of the deposits. A performance and geometric analysis of the depositions are also presented. Sound aluminum coatings were produced; plastic deformation and heat generation promotes a dynamic recrystallization of the anisotropic consumable rod, resulting in a fine and homogeneous deposit, free of any previous deformation. The coating presented an increase in ultimate tensile strength and failure deformation of 9% and 6%, respectively. Deposition efficiency between 25 and 50% were obtained, with a maximum of 48% average efficiency observed with 800RPM, 12kN and 16mm/s.